Saindo dos trilhos: os ferroviários riograndinos durante a ditadura civil-militar (1960-1970) - Friderichs, Lidiane Elizabete (2013)
This study will analyse how the railway worker/trade union movement was organized in the city of Rio Grande/RS before and after the civil-militar coup of 1964. The main objective will be to understand how the dictatorship has affected the organization of these workers and how they structured their trade union actions after its implantation.